Implementasi Amaliyah Ubudiyah dalam Membentuk Karakter Religius di Madrasah Aliyah Swasta Pesantren Temulus - Muhamad Bahrul Huda; Luluk Muasomah; Sadiran Sadiran (LP. Ma'arif Janggan Magetan, 2024)
This research aims to provide a detailed description of how the amaliyah ubudiyah program is implemented at the MA Pesantren Temulus in the Ngawi area to influence the religious character of students. This research uses a descriptive qualitative approach. Data was collected through interviews, observation, and documentation. Bearing in mind the conclusions of this research, the Amaliyah Ubudiyah character formation program at the Temulus Islamic Boarding School begins with classroom learning using materials relevant to the course outline, syllabus, and RPP and continues with implementation through reflection. 5S (Sapa et al.) is fostered through the Amaliyah Ubudiyah program, as is appropriate clothing (neat, clean, covering the private parts), duha (prayer), reverence for predecessors, heroes, and religious figures, and reading. Friday Koran, Friday cleaning, PHBI, closing class prayer, congregational prayer during the day, keeping the school clean, and obeying the rules.